When Reducing Low‐Value Care in Hospital Medicine Saves Money, Who Benefits?. Issue 1 (22nd November 2017) - Liao, Joshua M.; Navathe, Amol S.; Schapira, Marilyn M.; Weissman, Arlene; Mitra, Nandita; Asch, David A.
Abstract : One emerging policy solution for deterring low‐value care is to financially penalize physicians who prescribe it. However, physicians' willingness to support such policies may depend on whether they perceive that benefits accrue to patients or to insurers and hospitals. We surveyed physicians practicing hospital medicine to evaluate the association between policy support and physician beliefs about who benefits from the money saved through reducing low‐value services in hospital medicine. Overall, physicians believed that more of any money saved would go to profits and leadership salaries for insurance companies and hospitals and/or health systems rather than to patients. These beliefs were associated with policy support: 66% of those supporting physician penalties were more likely to believe that benefits accrue to patients or physicians, compared to 39% of those not supporting policies ( P < 0.001). Our findings are consistent with a sense of healthcare justice, in which physicians are less likely to support penalties imposed on themselves if the resulting benefits accrue to corporate or organizational interests. Effective physician penalties will likely need to address the belief that insurers and provider organizations stand to gain more than patients when low‐value care services are reduced.